Upaya Peningkatan Hasil Belajar Tematik Melalui Perpustakaan Sebagai Media - Erlina, Erlina (JURNAL GLOBAL EDUKASI, 2019)
Abstract: This class action research aims to improve the quality of learning through the library as a medium for Thematic theme Budi Pekerti Class I Students SDN 018477 B.P. Mandoge discrit Bandar Pasir Mandoge academic year 2018/2019. This research was conducted in grade I SDN 018477 B.P. Mandoge of 20 students. Learning outcomes in the first cycle reached 75% mastery learning after cycle I and cycle II, the mastery learning reflection and recommendations reached 85.29%. It can be concluded an increase in student learning outcomes through the library as a media on thematic learning. Keywords: library, media, character Abstrak: Penelitian tindakan kelas ini bertujuan untuk meningkatkan kualitas pembelajaran melalui perpustakaan sebagai media pada pelajaran Tematik tema Budi Pekerti Siswa Kelas I SDN 018477 B.P. Mandoge Kec. Bandar Pasir Mandoge T.P. 2018/2019. Penelitian ini dilaksanakan di kelas I SDN 018477 B.P. Mandoge yang berjumlah 20 orang siswa. Hasil belajar pada siklus I mencapai ketuntasan belajar 75% setelah siklus I dan siklus II, refleksi dan rekomendasi ketuntasan belajar mencapai 85,29%. Dapat disimpulkan terjadi peningkatan hasil belajar siswa melalui perpustakaan sebagai media pada pelajaran tematik. Kata Kunci: perpustakaan, media, budi pekerti